2008
DOI: 10.1007/s00114-008-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

Stenusine, an antimicrobial agent in the rove beetle genus Stenus (Coleoptera, Staphylinidae)

Abstract: Stenusine is well known as the alkaloid, discharged by the rove beetle, genus Stenus Latreille (Coleoptera, Staphylinidae). The Stenus beetles employ the alkaloid as an escape mechanism when on water surfaces. In the case of danger, they lower their abdomen and emit stenusine from their pygidial glands. Stenusine shows a low surface tension and therefore a high spreading pressure; these properties propel the beetle quickly over the water. Many Steninae do not live in habitats with open waters, but in detritus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Care of the body surface is thought to be important for disease prevention by elimination of pathogens [10, 11], fungi [12], and also parasites and parasitoids [13, 14]. Along with listed above, grooming is used to spread some substances throughout the integuments [11, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Care of the body surface is thought to be important for disease prevention by elimination of pathogens [10, 11], fungi [12], and also parasites and parasitoids [13, 14]. Along with listed above, grooming is used to spread some substances throughout the integuments [11, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…The pygidial gland constituents stenusine (4) and norstenusine (5) have antimicrobial activity. According to our study (Lusebrink et al, 2008), agar diffusion tests with a 57:43 (v/v) blend of (Z)- (1) and (E)-3-(2-methyl-1-butenyl)-pyridine (2) showed that the blend of 1 and 2 has higher antimicrobial properties at a content of 800 μg/disc than stenusine on in- Table I. Stenus species in which Z/E-isomers of 3-(2-methyl-1-butenyl)-pyridine (1, 2), 3-(1-isobutenyl)-pyridine (3), and stenusine (4) were detected by GC-MS. Brought to you by | MIT Libraries Authenticated Download Date | 5/10/18 5:34 PM sect pathogenic bacteria (Gram-positive: Bacillus sphaericus; Gram-negative: E. coli and Serratia entomophila).…”
Section: Biological Functionmentioning
confidence: 86%
“…Many beetle species secrete a variety of compounds from pygidial glands, compounds which have multiple functions in nature and have been the subject of numerous studies (Pasteels et al 1983;Witz and Mushinsky 1989;Kanehisa and Tsumuki 1996;Schultz and Puchalski 2001;Attygalle et al 2004;Francke and Dettner 2005;Holliday et al 2012;Schierling et al 2012). These compounds comprise a wide range of volatiles including carboxylic acids, carbonyl compounds, and alcohols, as well as simple aromatic compounds, derivatives of amino acids and hydrocarbons (Classen and Dettner 1983;Davidson et al 1989;Kelley and Schilling 1998;Will et al 2000;Francke and Dettner 2005;Lusebrink et al 2008). Dettner (1985) lists three functions of the pygidial gland secretions of Gyrinid beetles (Coleoptera: Gyrinidae): (a) to prevent microorganisms from attaching to the body, (b) to repel predators, and (c) to increase the wettability of the beetle's integument.…”
Section: Introductionmentioning
confidence: 99%